KNOWLEDGE, ATTITUDES AND PRACTICES OF PROFESSIONALS RELATED TO HIV PROPHYLAXIS: INTEGRATIVE REVIEW - de Oliveira Guedes, Maiker; do Nascimento, Bárbara Guimarães; dos Santos, Lucas Cardoso; Andrade, Juliane [UNESP] (Revista Baiana de Enfermagem, 2024)
Objective: to identify the knowledge, attitudes and practices of health professionals about pre- and post-sexual HIV prophylaxis. Method: review carried out in the databases CINAHAL, LILACS, Pubmed, WoS, Scopus and Google Scholar, in the languages Portuguese, English, French and Spanish, without time cut. Results: 45 articles were included, published between 2004 and 2023, in which professionals declared to have unsatisfactory knowledge about the pre- and post-sexual exposure prophylaxis, although they expressed a desire to receive training on the subject. As for attitudes, the scenario was divided between those who said they were willing to prescribe and those who did not show themselves available. The practices demonstrated services with little prescription, fragile advice and poor testing, reflected by stigmatized attitudes. Final considerations: the findings reinforce the need for the inclusion of the theme in vocational training and in continuing education actions.
CONOCIMIENTO, ACTITUDES Y PRÁCTICAS DE LOS PROFESIONALES RELACIONADOS CON LAS PROFILAXIS DEL VIH: REVISIÓN INTEGRATIVA
CONHECIMENTO, ATITUDES E PRÁTICAS DOS PROFISSIONAIS RELACIONADOS ÀS PROFILAXIAS DO HIV: REVISÃO INTEGRATIVA
Keywords: Health Personnel; HIV; Post-Exposure Prophylaxis; Pre-Exposure Prophylaxis; Review